The center-of-mass in Einsteins theory of gravitation - Beiglböck, Wolf Dieter (Communications in mathematical physics, 1967)
We prove the existence and uniqueness of a center-of-mass line as well as a center-of-motion line, the latter due toG. Dixon, 1964. The validity of the theorems depends on some assumptions listed in § 2, whose most restrictive ones (in the sense of physics) state a certain weakness of the gravitational field. In the concluding paragraph we give some corrolaries and a very simple application to the problem of motion.
Gesehen am 07.05.2018